THE INTERCONNECTION OF THE COUNTRY’S CYBER SECURITY AND INNOVATION POTENTIAL DURING INNOVATION TRANSFER AND IMPLEMENTATION - Koibichuk, Vitaliia; Slavhorodska, Kateryna; Samoilikova, Anastasiia; Mayboroda, Tetyana; Artyukhov, Artem (Socio-economic relations in the digital society, 2024)
The article is devoted to the investigation of the relationship between innovation and cyber security in the context of forecasting and reducing risks related to cyber security during the implementation of innovations. The purpose of the study is to confirm and model the interconnection between the levels of innovation development and cyber security of the country. The work describes the concept of innovation risk and the importance of cyber security in the modern world as one of the important factors in overcoming innovation risks. The current state of cyber security was analysed based on various indices, and the impact of cyber threats on innovation processes was investigated based on a sample from 26 countries of the world. This made it possible to identify leaders and outsiders in this field, as well as trends in the development of cyber security in dynamics. It is well-founded that cyber security is a key factor for the development and implementation of innovations. To confirm the existing relationship between cyber security and innovation, the multiple correlation coefficient was calculated, and an econometric model was built using the built-in functions of MS Excel (the estimation of the model parameters was carried out using the method of least squares using the built-in "Data Analysis" package of the MS spreadsheet editor Excel for a multivariable linear model). The significance of the model was confirmed by the coefficient of determination, Fisher’s test, and the level of significance of the p-value. The results of the study can be used to develop effective cyber defence strategies and contribute to the stable development of technologies in the face of growing cyber threats.